2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5332557
|View full text |Cite
|
Sign up to set email alerts
|

Detection of nocturnal frontal lobe seizures in pediatric patients by means of accelerometers: A first study

Abstract: The monitoring of epileptic seizures is mainly done by means of video/EEG-monitoring. Although this method is considered as the golden standard, it is not comfortable for the patient as the EEG-electrodes have to be attached to the scalp which hampers the patient's movement. This makes long term home monitoring not feasible. A detection system with accelerometers attached to the wrists and ankles can solve this problem. Nocturnal frontal lobe seizures often include bicycle pedaling movements or uncontrolled mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 5 publications
0
39
0
Order By: Relevance
“…An alarm system, capable of detecting seizures, could alert relatives and caretakers and ensure help for the patient. Several groups [1], [2] have already tried to develop such a system based on motion data, but none of them is performing well enough to reach clinical use. We therefore propose a new automatic detection algorithm capable of capturing the seizures with motor manifestations, without too many false alarms.…”
Section: Introductionmentioning
confidence: 99%
“…An alarm system, capable of detecting seizures, could alert relatives and caretakers and ensure help for the patient. Several groups [1], [2] have already tried to develop such a system based on motion data, but none of them is performing well enough to reach clinical use. We therefore propose a new automatic detection algorithm capable of capturing the seizures with motor manifestations, without too many false alarms.…”
Section: Introductionmentioning
confidence: 99%
“…The algorithm detected all the motor events, and 43-89% of the detections was correct. Jallon et al [9] and Cuppens et al [6] also studied the detection of epileptic seizures with accelerometers and Conradsen et al [4] used a multi-modal approach. In our approach, we detect the movement contactless, which is more comfortable for the patient.…”
Section: Introductionmentioning
confidence: 98%
“…A new device for warning about seizures is therefore needed. Several groups have worked on detecting seizures based on ACM data [1], [6], [7]. Nijsen et al [ have shown that in a test on 18 patients it was possible to detect the seizures of 10 patients based on visual inspection of ACM data.…”
Section: Introductionmentioning
confidence: 99%